2015
DOI: 10.1007/s11427-015-4858-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between retinal neuronal degeneration and visual function impairment in type 2 diabetic patients without diabetic retinopathy

Abstract: The changes in retinal thickness and visual function in type 2 diabetic patients without clinical evidence of diabetic retinopathy were evaluated. A total of 141 diabetic subjects without retinopathy and 158 healthy subjects were enrolled in this study. Superior macular ganglion cell complex thicknesses were significantly decreased in diabetic cases, and no significant peripapillary retinal nerve fiber layer thickness changes were observed. The contrast sensitivities at all space frequencies were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 44 publications
2
21
2
3
Order By: Relevance
“…These results support previous findings, where loss of contrast sensitivity in type 2 diabetics who do not have diabetic retinopathy was hardly observed [5,14,16]. However, other researchers have found changes affecting CSV in all frequencies in patients with DM2 and no retinopathy [15,17]. It has been suggested that the selective loss of contrast sensitivity for the higher frequencies is a signal of parvocellular dysfunction [18]; this would account for 80% of the retinal ganglion cells (which are parvocellular) [19].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results support previous findings, where loss of contrast sensitivity in type 2 diabetics who do not have diabetic retinopathy was hardly observed [5,14,16]. However, other researchers have found changes affecting CSV in all frequencies in patients with DM2 and no retinopathy [15,17]. It has been suggested that the selective loss of contrast sensitivity for the higher frequencies is a signal of parvocellular dysfunction [18]; this would account for 80% of the retinal ganglion cells (which are parvocellular) [19].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the evaluation of CSV in different spatial frequencies is of great importance in these patients. It appears that, in the presence of clinical diabetic retinopathy, a decrease in contrast sensitivity is present [5,14], which may be independent of the visual acuity affectation [5,15].…”
Section: Discussionmentioning
confidence: 98%
“…It is estimated that implementation of the Vision 2020 will result in the prevention of blindness in 429 million people and 102 billion dollars of economic benefit. 22 Refractive errors were the leading cause of visual impairment in our study, both in the younger and the older age groups. This finding is similar to other studies.…”
Section: Discussionmentioning
confidence: 58%
“…Vascular abnormalities and neuronal alterations accompany the pathogenic changes at the earliest stages of diabetic retinopathy, including neural apoptosis, loss of ganglion cells, glial reactivity, and a reduction in the thickness of the inner retinal layers [31]. Capillary obstruction due to leukostasis as well as capillary dropout due to the death of vascular pericytes and endothelial cells lead to tissue ischemia, which triggers the accumulation of a number of proangiogenic factors, including VEGF, erythropoietin, Ang-2, and SDF-1 [24].…”
Section: Dme As An Inflammatory Diseasementioning
confidence: 99%